Question about Collect
- To: mathgroup at smc.vnet.net
- Subject: [mg71273] Question about Collect
- From: "dimitris" <dimmechan at yahoo.com>
- Date: Sun, 12 Nov 2006 06:48:51 -0500 (EST)
Consider the following simple expression expr = Collect[x^3 - c*x^2 - 3*a*x - b /. x -> y + c/3, y] -b - a*c - (2*c^3)/27 + (-3*a - c^2/3)*y + y^3 I can't understand the difference between the two outputs below expr /. {-b - a*c - (2*c^3)/27 -> A1, -3*a - c^2/3 -> A2} A1 + (-3*a - c^2/3)*y + y^3 (*and*) expr /. -b - a*c - (2*c^3)/27 -> A1 /. -3*a - c^2/3 -> A2 A1 + A2*y + y^3 I waited to be the same. Any guidance/insight? Dimitris